Diagnostic Value of Magnetic Resonance Imaging in Thoracic Outlet Syndrome. (August 2014) - Singh, Vinay Kumar; Jeyaseelan, Luckshmana; Kyriacou, Steve; Ghosh, Subhojit; Sinisi, Marco; Fox, Michael
Purpose: To evaluate the diagnostic value of magnetic resonance imaging (MRI) in thoracic outlet syndrome (TOS). Methods: Medical records of 30 women and 10 men aged 18 to 68 (mean, 38) years who presented with unilateral (n=35) and bilateral (n=5) TOS and underwent 42 surgical decompressions of the right (n=23) and left (n=19) sides were reviewed. MRI findings were compared with intra-operative findings to evaluate the diagnostic value of MRI. Results: MRI findings correlated poorly with intraoperative findings. Of the 42 cases, MRI and intraoperative findings were matched in 17 and not matched in 25. MRI appeared normal but intraoperative findings were in fact positive for TOS in 23 of 24 cases. The sensitivity and specificity of MRI in diagnosing TOS were 41% and 33%, respectively, whereas its positive and negative predictive values were 89% and 4%, respectively. Conclusion: Sensitivity and specificity of MRI in diagnosing TOS are low. Diagnosis should be based on a holistic approach including history, clinical examination, and radiological findings.